Stereotactic focal radiotherapy as an alternative treatment for low-risk prostate cancer: Results of a single-arm monocenter Phase-II trial - Nguyen, Paul V.; Donneaux, Bertrand; Louis, Céline; Bodgal, Zsuzsa; Philippi, Sven; Biver, Sylvie; Frederick, Bérangère; Harzé, Ludovic; Lasar, Yves; Vogin, Guillaume; Nickers, Philippe (Frontiers in Oncology, 2023)
Introduction: Since standard prostate-cancer treatments do not alter overall survival, preserving quality of life (QOL) remains the key objective. Active surveillance of indolent prostate cancer avoids curative treatment side-effects but necessitates repeated biopsies. Stereotactic body radiation therapy (SBRT) may be an alternative. This non-randomized Phase-II trial examined the feasibility and safety of SBRT for low-favorable intermediate-risk prostate cancer. Methods: Patients were recruited in 2016–2019 if they had: localized CAPRA<3 prostate adenocarcinoma; an isolated PIRADS>4 macroscopic tumor on MRI; WHO Performance Status 0-1; and no major urinary symptoms. 36.25Gy (80% isodose prescription) was delivered in 5 fractions every other day. Primary outcome was delay between SBRT and salvage-treatment initiation. Secondary outcomes were: acute/late genitourinary/rectal toxicity; biological, clinical, and MRI control; and change in QOL measures. Results: Over a median follow-up of 36 months, salvage prostatectomy in the 24 eligible patients was never required. Three-year biochemical progression-free survival was 96%. The single biochemical recurrence was a small (2-mm) Gleason 6 (3+3) lesion in the non-irradiated lobe. All 19 patients with ≥1 post-treatment MRI evaluations demonstrated complete radiological response. Acute/late grade ≥3 toxicities did not occur: all acute toxicities were grade-1 genitourinary (38% patients), grade-2 genitourinary (8%), or grade-1 rectal (13%) toxicities. There was one (4%) transient late grade-1 genitourinary toxicity. QOL was unchanged at last follow-up, as shown by IPSS (2.86 to 3.29, p>0.05), U-QOL (0.71 to 0.67, p>0.05), and IIEF5 (the 14 initially potent patients maintained potency). Conclusion: SBRT is feasible, well-tolerated, and preserves QOL. This innovative robotized approach challenges active surveillance.